1,3,5-Triazine-cored maltoside amphiphiles for membrane protein extraction and stabilization - Ghani,L; Munk,CF; Zhang,X; Katsube,S; Du,Y; Cecchetti,C; Huang,W; Bae,HE; Saouros,S; Ehsan,M; Guan,L; Liu,X; et al. (Journal of the American Chemical Society, 2019)
Despite their major biological and pharmacological significance, the structural and functional study of membrane proteins remains a significant challenge. A main issue is the isolation of these proteins in a stable and functional state from native lipid membranes. Detergents are amphiphilic compounds widely used to extract membrane proteins from the native membranes and maintain them in a stable form during downstream analysis. However, due to limitations of conventional detergents, it is essential to develop novel amphiphiles with optimal properties for protein stability in order to advance membrane protein research. Here we designed and synthesized 1,3,5-triazine-cored dimaltoside amphiphiles derived from cyanuric chloride. By introducing variations in the alkyl chain linkage (ether/thioether) and an amine-functionalized diol linker (serinol/diethanolamine), we prepared two sets of 1,3,5-triazine-based detergents. When tested with several model membrane proteins, these agents showed remarkable efficacy in stabilizing three transporters and two G protein-coupled receptors. Detergent behavior substantially varied depending on the detergent structural variation, allowing us to explore detergent structure–property–efficacy relationships. The 1,3,5-triazine-based detergents introduced here have significant potential for membrane protein study as a consequence of their structural diversity and universal stabilization efficacy for several membrane proteins.